Pengembangan Media Video Pembelajaran Huruf Hiragana di SMAN 1 Krembung - Ari Edi Handayani; Rufi’i Rufi’i; Hartono Hartono (Departement of Mathematics Education, 2024)
This research aims to develop Hiragama Letter Learning Media in the Krembung 1 Public High School Environment. In this research, researchers used Research and Development (R&D). The data collection technique was carried out in stages by being tested by experts (expert validation) involving design experts, material experts and colleagues. The validation results were then tested in small groups, limited groups and field trials. Based on the research data and discussions that have been described, it can be concluded that the development of video media for learning Hiragana letters was obtained from validity tests by media experts, design experts and material experts in measuring feasibility, namely in the feasible category. And from the opinions of class Thus, the Hiragana letter learning video development product can be categorized as suitable for use at SMAN 1 Krembung.